2022
DOI: 10.1159/000526851
|View full text |Cite
|
Sign up to set email alerts
|

Brolucizumab Intravitreal Injection in Macular Neovascularization Type 1: VA, SD-OCT, and OCTA Parameter Changes during a 16-Week Follow-Up

Abstract: Purpose: to assess the anatomical and functional changes after brolucizumab intravitreal injection (BIVI) in macular neovascularization type 1 (MNV1). Setting/Venue: Ophthalmology Clinic, University "G. d'Annunzio" of Chieti-Pescara. Methods: A total of 24 eyes of 24 patients suffering from naïve MNV1 candidates to BIVI as per label with q12/q8 dosing regimen after the loading dose were enrolled in this prospective study. Main outcome measures during a 16-weeks follow up period included changes of best correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
3
4
0
Order By: Relevance
“…As regards naïve patients, we showed a statistical reduction of PED-MH after the loading phase. This is in accordance with Toto et al 18 , who demonstrated a significant reduction between baseline and week 16 in naïve type 1 MNV. Thanks to our longer follow-up, the maintenance of the statistical result at week 24 and the last follow-up could also be demonstrated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As regards naïve patients, we showed a statistical reduction of PED-MH after the loading phase. This is in accordance with Toto et al 18 , who demonstrated a significant reduction between baseline and week 16 in naïve type 1 MNV. Thanks to our longer follow-up, the maintenance of the statistical result at week 24 and the last follow-up could also be demonstrated.…”
Section: Discussionsupporting
confidence: 93%
“…Mishra et al demonstrated that both IRF and SRF were detected in 82.1% of patients at baseline; after the loading phase, they reduced respectively to 41.1% and 16.1% 22 . Toto et al 18 showed a reduction in IRF and subfoveal-SRF rates in type 1 MNV between baseline and week 12, respectively changing from 41.7 to 20.8% and from 62.5 to 4.2%. The greater amount of unresponsive fluid in the intraretinal compartment may represent a biomarker of degenerative cystoid processes 23 .…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with our previous results, the 1-year followup confirmed the efficacy of brolucizumab in patients with G1 by observing improved BCVA and reduction of CMT and SCT [13]. CMT has been considered a validated biomarker of activity and final endpoint for different studies [16,17].…”
Section: Discussionsupporting
confidence: 88%
“…In our previous work, brolucizumab demonstrated to be efficient in a 16-week interval in patients with naïve G1 in reducing OCT and OCT-A biomarkers mirror of the disease activity and improving visual acuity with overall patient satisfaction [13]. The aim of our new study was to analyze structural and morphofunctional changes occurring in naïve eyes with G1 and G2 treated with brolucizumab in a 1-year interval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation